PEMBAGIAN HARTA WARISAN PERSPEKTIF KEADILAN GENDER: DIALEKTIKA PEMIKIRAN HUKUM ISLAM, ADAT, DAN KONTEMPORER - Tarmizi, Tarmizi; Ansar, Lukman (Universitas Islam Negeri Alauddin Makassar, 2026)
Gender justice in the distribution of inherited assets continues to be a topic of discussion among various groups, despite existing provisions in inheritance law. The emergence of various perspectives advocating for gender-based justice in inheritance indicates a demand for equal rights between men and women without being bound by existing legal provisions. This study examines the dialectic of inheritance distribution based on gender justice through Islamic legal thought, customs developed within society, and contemporary paradigms advocating for gender equality. This study was conducted as a literature review using a conceptual approach and data collection through relevant key literature, which was then analyzed using descriptive qualitative methods. The results indicate a convergence of thought among Islamic law, customary law, and contemporary paradigms in proposing a concept of inheritance distribution grounded in gender equality. Conceptually, Islamic legal scholars have dared to propose an inheritance system with equal shares between men and women. From the perspective of customary law, the flexibility in determining shares based on agreement opens opportunities for female heirs to receive the same share as men. Similarly, contemporary paradigms pioneered through social and political movements and policy formulations advocate for gender equality on a global scale. This study offers a conceptual contribution regarding the importance of gender equality, including in the distribution of inherited assets, through various theoretical frameworks.